VD_FINDINFO HC / 2012 / 723 vom 12. Oktober 2012 - VD Tribunal cantonal (2012)
MESURE PROVISIONNELLE, DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT | 137 al. 2 CC, 176 al. 1 ch. 1 CC, 176 al. 3 CC, 276 al. 2 CC, 285 al. 1 CC, 6 par. 1 CEDH, 12 Cst., 29 al. 2 Cst., 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 316 al. 1 CPC (CH), 317 al. 1 CPC (CH)